Effectiveness of Time Perspective Therapy on Increasing Psychological Well-Being and Happiness in Veterans with PTSD - M. Malekiha; B. Moradi (Afarand Scholarly Publishing Institute, 2019)
Aims: Time perspective therapy is one of the modern treatments that in recent years has been used in order to decrease the symptoms of the disorder and increasing the quality of life in patients with PTSD. In this regard, the aim of the present study was to investigate the effectiveness of time perspective therapy on increasing the psychological well-being and happiness of veterans with PTSD. Materials & Methods: This quasi-experimental research with pretest-posttest design, with one control group, was carried out among the veterans with PTSD, who referred to the Amiralmomenin Hospital in Isfahan in 2017. Among them 30 people of veterans with PTSD were selected through convenient sampling method and randomly assigned into the control and experimental groups (n=15 in each group). Experimental group was treated in 8 sessions in 90 minutes with time perspective therapy while the control group received no cure. The research instruments were the Oxford happiness questionnaire and Ryff psychological well-being questionnaire, which were completed in two stages of pretest and posttest. Data were analyzed using SPSS 23 software, through one-way analysis of covariance and multivariable analysis of covariance tests. Findings: By controlling the effect of pretest, there was a significant difference between the mean scores of psychological well-being and happiness of veterans with PTSD in the control and experimental groups in the posttest step (p<0.05). Conclusion: Time perspective therapy can be effective in increasing the psychological well-being and happiness of veterans with PTSD.